EDUCATIONAL RESPONSIBILITY: POINTS AND COUNTERPOINTS - Neves, Danilo Trombetta; Di Giorgi, Cristiano Amaral Garboggini [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2016)
This article comprises of the research on the bills dealing on educational responsibility, with emphasis on promotion of basic public education with minimum quality standard. The methodology was the documentary analysis. The aim lies in checking possible assistance of a law of responsibility for the improvement of public basic education quality. The survey showed that projects are deficient with regard to the promotion of education, being overcome by the current National Education Plan. Moreover, we note that the fundamental right to basic public education constitutes a barrier to legislative setback, mainly so they are not considered suspension of voluntary transfers from the Union to other federal agencies, even if the targets unreached in national evaluation process.
Keywords: Educational Responsibility; Basic Education publishes; Promotion of Education; Evaluation; Financing